A new class of ribozyme from hepatitis B virus. (April 2017) - Lim, Chun Shen; Brown, Christopher
Abstract : In this issue, Chakraborty and Ghosh present initial in vitro data indicating a 53‐base part of the hepatitis B virus (HBV) epsilon region is a ribozyme with unusual properties. Self‐cleavage first occurred at the HBV non‐canonical polyadenylation signal UAUAAA and the "centre bulge" of the epsilon region, releasing a ribozyme. The released ribozyme then acted as a new class of trans‐cleaving ribozyme cleaving other RNAs.